Transparent conductive elastomers with excellent autonomous self-healing capability in harsh organic solvent environments. Issue 10 (25th February 2020) - Li, Ren'ai; Chen, Guangxue; Fan, Ting; Zhang, Kaili; He, Minghui
Abstract : A new type of transparent conductive elastomer with excellent autonomous self-healing capability in harsh organic solvent environments is reported. Abstract : A new type of supramolecular elastomer, photopolymerized from two rationally designed polymerizable deep eutectic solvent (PDES) monomers, was reported. The resultant network was highly transparent, intrinsically conductive, stretchable, and self-healable. In particular, the healing process can even take place in various organic solvents, simultaneously with enhanced adaptability.